Reliability, usability and applicability of the ICD-11 beta draft focusing on hand injuries and diseases: results from German field testing. (14th December 2019) - Eisele, Angelika; Dereskewitz, Caroline; Oberhauser, Cornelia; Kus, Sandra; Coenen, Michaela
Abstract: Objective: To test the interrater reliability when using the codes of the 11th revision of the International Classification of Diseases (ICD)-11 beta draft as well as ICD-10 and to explore the usability of the ICD-11 beta draft and the applicability of ICD-11's Supplementary section for functioning assessment in hand injuries and diseases. Design: We conducted a validation study of the ICD-11 beta draft complemented by a single-centre study to collect clinical routine data on functioning. Setting: German hand surgery clinics. Participants: Twenty-three physicians coded real-life cases containing diagnostic information on hand injuries and diseases. Additionally, clinical information of 100 patients was coded by 6 physicians and a nurse using ICD-11's Supplementary section for functioning assessment. Main Outcome Measures: Physicians coded 210 cases using the ICD-11 beta draft and ICD-10. Krippendorff's alpha was calculated. Clinical routine data was coded using 38 functioning categories. Results: Interrater reliability (Krippendorff's alpha) of 0.67 for ICD-11 coding and 0.71 for ICD-10 coding was obtained, indicating substantial agreement. However, physicians reported a high proportion of problems with ICD-11 coding and slightly fewer problems with ICD-10 coding. The collected data on functioning could be mapped to ICD-11's Supplementary section for functioning assessment. For some data, however, only unspecific codes were available. Conclusions: Interrater reliability of ICD-10 and ICD-11 was satisfactory. Training material for ICD-11 is needed to further improve reliability and usability. Future users of ICD-11 should be encouraged to use the Supplementary section for functioning assessment to shed light on the problems patients experience in everyday life.